2018
DOI: 10.1111/myc.12738
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Candida albicans and Candida glabrata in biofilms: Influence of the strain type, culture medium and glucose supplementation

Abstract: The relationship among Candida species may be influenced by several factors. Thus, this study evaluated the interactions between Candida albicans and Candida glabrata in biofilms, varying the strain type, culture medium and glucose supplementation. Biofilms were formed for 48 hours in Sabouraud dextrose broth (SDB) or RPMI 1640, supplemented with 0%, 1% or 5% glucose. Each strain of C. albicans was combined with two strains of C. glabrata, generating four biofilm associations, which were quantified by colony-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
4
10
0
Order By: Relevance
“…In a previously‐published study, it was suggested that lower metabolic activity of biofilms, formed without glucose, could be related to the decrease of extracellular matrix production, which resulted in lower biomass . In addition, the results of the present study showed a significant impact of glucose levels on the production of extracellular polysaccharides by biofilm cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previously‐published study, it was suggested that lower metabolic activity of biofilms, formed without glucose, could be related to the decrease of extracellular matrix production, which resulted in lower biomass . In addition, the results of the present study showed a significant impact of glucose levels on the production of extracellular polysaccharides by biofilm cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a previously‐published study, the effect of glucose supplementation (55.5 and 277.7 mmol/L, respectively) on the viability of Candia albicans and Candia glabrata biofilms was evaluated . As with the present study, supplemented groups did not differ with regard to cell viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total biomass of single and mixed Candida biofilms was quantified by crystal violet (CV, Macklin, Shanghai, China) and the experimental procedures were performed with moderate modification as previously described (Hosida et al, 2018). Briefly, 100 μL strain-contained culture and 100 μL caspofungin-included medium were added into a 96-well plate at 37°C for 24 and 48 h. Following the formation of Candida biofilms, the supernatant was removed and 200 μL of 99% methanol (Suyi, Shanghai, China) for fixation at room temperature for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Once the balance is broken, dysbiosis occurs leading to microbial invasions and diseases. Although most studies showed that the co-culture of C. glabrata and C. albicans can improve their invasions into host tissue compared with their single cultures (Coco et al, 2008; Pathak et al, 2012; Alves et al, 2014; Tati et al, 2016), the reports on the competitive advantages of both Candida species during their co-culture and their mixed biofilm virulence compared with the single counterpart are contradictory (Silva et al, 2013; Rossoni et al, 2015; Hosida et al, 2018; Olson et al, 2018). Thus, it is consequential to illuminate the relationship between the individual Candida abundance and the virulence in C. albicans and C. glabrata mixed biofilms.…”
Section: Introductionmentioning
confidence: 99%